An Innovative Green Dust Suppressant for Dry Climate Mining Areas in a Copper–Nickel Mine: Integration of Moisture Retention and Erosion Resistance - Zijun Li; Zhe Zhou; Yu Xu; Yin Chen (Atmosphere)
Mine ramps, serving as a critical transportation hub in underground mining activities, are beset by severe issues of dust pollution and secondary dust generation. While dust suppressants are more efficient than the commonly used sprinkling methods in mines, traditional single-function dust suppressants are inadequate for the complex application environment of mine ramps. Building on the development of conventional single-function dust suppressants, this research optimized the components of bonding, wetting, and moisturizing agents. Through single-factor optimization experiments, a comparison was made of the surface tension water retention property and viscosity of diverse materials, thus enabling the identification of the primary components of the dust suppressant. By means of synergistic antagonism experiments, the optimal combination of the wetting agent and bonding agent with excellent synergy was ascertained. Ultimately, the wind erosion resistance and rolling resistance were measured through three-factor orthogonal experiments, and the optimal ratio of the dust suppressant was established. Specifically, fenugreek gum (FG) was selected as the bonding agent, cane sugar (CS) as the moisturizing agent, and alkyl phenol polyoxyethylene ether (Op-10) as the wetting agent. The research findings demonstrate that the optimal ratio of dust suppressant is 0.3 wt% fenugreek gum (FG) + 0.06 wt% alkyl phenol polyoxyethylene ether (Op-10) + 3 wt% cane sugar (CS). Under these conditions, the dust fixation rate can reach up to 97~98% at a wind speed of 8 m/s. The maximum rolling resistance can reach 65~73% after grinding the samples for 1 min. The surface tension of the solution is 13.74 mN/m, and the wetting performance improved by 81% compared to pure water. This dust suppressant is of great significance for improving the working environment of workers and ensuring the sustainable development of the mining industry.